A review on algorithms for maximum clique problems - Wu, Qinghua; Hao, Jin-Kao (European journal of operational research, 2015)
•We provide an updated review of exact and heuristic algorithms for maximum clique problems.•We classify the search strategies and put forward the key ingredients of the reviewed methods.•This is aimed to encourage more research on new solution algorithms.•This is aimed to motivate more applications of using clique approaches. The maximum clique problem (MCP) is to determine in a graph a clique (i.e., a complete subgraph) of maximum cardinality. The MCP is notable for its capability of modeling other combinatorial problems and real-world applications. As one of the most studied NP-hard problems, many algorithms are available in the literature and new methods are continually being proposed. Given that the two existing surveys on the MCP date back to 1994 and 1999 respectively, one primary goal of this paper is to provide an updated and comprehensive review on both exact and heuristic MCP algorithms, with a special focus on recent developments. To be informative, we identify the general framework followed by these algorithms and pinpoint the key ingredients that make them successful. By classifying the main search strategies and putting forward the critical elements of the most relevant clique methods, this review intends to encourage future development of more powerful methods and motivate new applications of the clique approaches.